2021
DOI: 10.1186/s12877-021-02279-7
|View full text |Cite
|
Sign up to set email alerts
|

The sex difference in gait speed among older adults: how do sociodemographic, lifestyle, social and health determinants contribute?

Abstract: Background This study explores whether a sex difference in sensitivity to (strength of the association) and/or in exposure to (prevalence) determinants of gait speed contributes to the observed lower gait speed among older women compared to men. Methods Data from the Longitudinal Aging Study Amsterdam (LASA) were used. In total 2407 men and women aged 55–81 years were included, with baseline measurements in 1992/2002 and follow-up measurements ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
(61 reference statements)
1
14
0
1
Order By: Relevance
“…In Bohannon's study, age, height, and waist circumference were found to be highly correlated with gait speed (7). In the cohort study that included 2407 participants by Sialino et al, female gender, lower education level, and having more chronic diseases were found to be associated with slower gait speed (28). In our study, we found that a high education level positively affected gait speed and shape.…”
Section: Discussionsupporting
confidence: 54%
“…In Bohannon's study, age, height, and waist circumference were found to be highly correlated with gait speed (7). In the cohort study that included 2407 participants by Sialino et al, female gender, lower education level, and having more chronic diseases were found to be associated with slower gait speed (28). In our study, we found that a high education level positively affected gait speed and shape.…”
Section: Discussionsupporting
confidence: 54%
“…Declined lower limb muscle function and fewer muscle fibers in female compared with male along with aging process and the attribution of the larger step and stride length in male may be the cause of this condition [ 27 , 28 ]. Other potential determinants have been proposed to account for gender differences in walking speed such as a greater change toward smaller fibers in females during aging-related atrophy [ 29 ], a substantial decrease in estrogen, a potent hormone improving the intrinsic quality of skeletal muscle [ 30 ], body composition [ 31 ] or lower level of physical activity [ 32 ]. Our study showed that a slow walking speed was significantly associated with high fall risk, ADL/IADL dependence and frailty syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible to assume that gait differences are less relevant to earlier episodes of depression. Additionally, gait changes are likely confounded by comorbidity with physical health disorders [ 10 , 38 ], the latter of which are less likely to be present in younger samples. In support, the majority of our study participants were physically active.…”
Section: Discussionmentioning
confidence: 99%